-5x+12=-3x+9

Simple and best practice solution for -5x+12=-3x+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5x+12=-3x+9 equation:


Simplifying
-5x + 12 = -3x + 9

Reorder the terms:
12 + -5x = -3x + 9

Reorder the terms:
12 + -5x = 9 + -3x

Solving
12 + -5x = 9 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
12 + -5x + 3x = 9 + -3x + 3x

Combine like terms: -5x + 3x = -2x
12 + -2x = 9 + -3x + 3x

Combine like terms: -3x + 3x = 0
12 + -2x = 9 + 0
12 + -2x = 9

Add '-12' to each side of the equation.
12 + -12 + -2x = 9 + -12

Combine like terms: 12 + -12 = 0
0 + -2x = 9 + -12
-2x = 9 + -12

Combine like terms: 9 + -12 = -3
-2x = -3

Divide each side by '-2'.
x = 1.5

Simplifying
x = 1.5

See similar equations:

| 6z+8z+9z-7= | | 4y=3y-4 | | 16a^2+8a-15=0 | | x-10x+1=0 | | -48a^3-24a^2+45a=0 | | 2x^3-x^2+8x-4=0 | | 3(a/6+3)+1/2(a+6a) | | 49c^2-84cr+36r^2=0 | | 3x-6/15x | | 36=4w+4(w+5) | | 56s^2+19st-15t^2=0 | | -1=7x+4(x-3) | | -4=-8y+2(y+4) | | -2+8s^2+3s^4=0 | | -2u+4(u-2)=-4 | | 4x(x+2)+11-4=2x+3 | | 12s^4+32s^2-8=0 | | 5(x-5)-6x=-2 | | 7/12*9/2-33/40 | | (2x^2-6x-8)/(x+1) | | 3s^4+8s^2-2=0 | | 7/x+3-5/x-3=3x/x^2-9 | | 14x^2/7x | | -13+6=m-10 | | 6v^2+3v-4=-4v^2 | | 3a^2-14a-5=0 | | 2v^2+3v-4=0 | | -13+6=m-16 | | y=-1*1 | | 7/12x9/2-33/40 | | 4/5b=120 | | 4/5b=48 |

Equations solver categories